2016
DOI: 10.29252/ijnv.5.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Leadership skills is necessary for extra roles behaviors and professional excellence

Abstract: Introduction:Undoubtedly create or strengthen the leadership skills in personnel to meet the future professional needs and as one of the development and professional excellence factors in complex organizations such as health care system. But create or strengthen the leadership skills in personnel need to understand the various aspects and factors affecting it. Aim: This study designed with content analysis approach to explain the main component of leadership skills in the nursing profession. Method: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Managers cannot monitor all situations; therefore, the nurses and physicians should be treated in a way that they provide appropriate care without the presence of supervisors and nurse managers. 15 A good understanding of staff conditions and effective communication were the most important sub-themes of people-oriented management in the present study. Zaimi et al 32 also stated that “relationship orientation” was important from nurse managers’ perspectives.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Managers cannot monitor all situations; therefore, the nurses and physicians should be treated in a way that they provide appropriate care without the presence of supervisors and nurse managers. 15 A good understanding of staff conditions and effective communication were the most important sub-themes of people-oriented management in the present study. Zaimi et al 32 also stated that “relationship orientation” was important from nurse managers’ perspectives.…”
Section: Discussionmentioning
confidence: 58%
“…30 In general, he referred to compassion, patience, observance of justice, secretiveness, trustworthiness, and work conscience. 19 Rezapour Nasrabad 15 pointed to patience and secretiveness as the major characteristics of managers and regarded them as the spiritual capacity to accept science, power, as well as all perceptions and feelings. Work conscience was one of the most important sub-themes of ethics.…”
Section: Professional Ethicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants viewed that the transfer of knowledge and the teaching of ethics to their colleagues, in particular to junior counterparts, play a pivotal role in developing the next generation of competent professionals, which in turn elevates performance levels and the sustainability of treatment centers. A previous study concluded that knowledge transfer by nurses to their colleagues indicates the presence of optimal leadership skills (58). Unfortunately, the provision of medical information to patients and their family caregivers is often neglected by the OR personnel, although it is a part of the Iranian patient's rights charter (59).…”
Section: Discussionmentioning
confidence: 99%